Counting Cows - Sheldon, Dyan And Smith, Wendy (London Random House, 2000)
Dara can't sleep. Dad suggests they count sheep. But Dara doesn't like sheep, she likes cows. So they count cows. Try as he might, though, Dad just can't get Dara's cows to jump the fence, mostly because one very lively, mischievous cow isn't
Include Color Illustrations
Keywords: Counting -- Cows